Macrophages overexpressing interleukin‐10 target and prevent atherosclerosis: Regression of plaque formation and reduction in necrotic core - Mingyi Wang; Shanshan Zhou; Yingyun Hu; Wei Tong; Hao Zhou; Mingrui Ma; Xingxuan Cai; Zhengbin Zhang; Luo Zhang; Yundai Chen (Bioengineering & Translational Medicine)
Abstract Atherosclerosis, a slowly progressing inflammatory disease, is characterized by the presence of monocyte‐derived macrophages. Interventions targeting the inflammatory characteristics of atherosclerosis hold promising potential. Although interleukin (IL)‐10 is widely acknowledged for its anti‐inflammatory effects, systemic administration of IL‐10 has limitations due to its short half‐life and significant systemic side effects. In this study, we aimed to investigate the effectiveness of an approach designed to overexpress IL‐10 in macrophages and subsequently introduce these genetically modified cells into ApoE−/− mice to promote atherosclerosis regression. We engineered RAW264.7 cells to overexpress IL‐10 (referred to as IL‐10M) using lentivirus vectors. The IL‐10M exhibited robust IL‐10 secretion, maintained phagocytic function, improved mitochondrial membrane potentials, reduced superoxide production and showed a tendency toward the M2 phenotype when exposed to inflammatory stimuli. IL‐10M can selectively target plaques in ApoE−/− mice and has the potential to reduce plaque area and necrotic core at both early and late stages of plaque progression. Moreover, there was a significant reduction in MMP9, a biomarker associated with plaque rupture, in IL‐10M‐treated plaques from both the early and late intervention groups. Additionally, the administration of IL‐10M showed no obvious side effects. This study serves as proof that cell therapy based on anti‐inflammatory macrophages might be a promising strategy for the intervention of atherosclerosis.